MAKNA DAN FUNGSI RITUAL ADAT “DABBA ANA” PADA MASYARAKAT JINGITIU, DI DESA WADUWALLA KECAMATAN SABU LIAE, KABUPATEN SABU RAIJUA. KAJIAN : SEMIOTIK - Malay, Narantoputrayadi Makan; Padji, Yeni (Jurnal Lazuardi, 2021)
This thesis is entitled “The meaning and Function of Dabba Ana Traditional Ceremony in Jingitiu Community at Waduwalla Village, Sabu Liae Sub-District, Sabu Raijua District. Tthis research is conducted to describe The Meaning and function of Dabba Ana Traditional Ceremony using Charles Sanders Pierre’s Semiotic Theory which is emphasized on : (1) sign icon which has same meaning with the appointed meaning inherently, (2) sign index which has casual relation to the appointed sign, and (3) a sign of symbol which has meaning relation to the appointed arbiter sign, the method which is used in conducting this research is descriptive qualitative . Describtive qualitative method can be defined as a research method without using numbers but words or sentences. The result of this research showed that The Meaning and Function of Dabba Ana Traditional Ceremony is a form of life change or self surrender from Jingitiu Community to God as the life giver based on their believes.